Gottes Haus : Untersuchungen zur Kirche als heiligem Raum von der Spätantike bis ins Frühmittelalter - Czock, Miriam (2012)
Using the idea that church buildings are sacred spaces, this study seeks to examine a central figure of thought in medieval society, the "ecclesia". Using normative, liturgical, and exegetic-theological sources, the book traces the profound transformational process that took place in the political and religious view of society from Late Antiquity to the Early Middle Ages. The study describes the dynamics that led to the development of a ecclesiology with a powerful impact on an entire epoch.